(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Based on the data from clinical observation of a higher incidence of cataracts in patients with glaucoma, conduction of the experimental studies on the development of age-related cataract on the background of ocular hypertension is of particular relevance. Purpose. To investigate peculiarities of modeling age-related cataract in the conditions of ocular hypertension. Methods. Studies were conducted on 27 rabbits. The experimental animals were divided into 3 groups; I — modeled light cataract, II — reproduced hypertension, III — before light irradiation they were induced hypertension. Results. On the 5th week of the development of experimental cataract on the background of hypertension there is already partially formed opacity in all the lenses. On the 10th week, all lens became more opaque cloudy. In experiments with light exposure without ocular hypertension primary opacity appeared in the lens only on the 10th week, and on the 20th week of the experiment 1/3 lens remained clear and development of opacities (I — III stage) was noted in 2/3 lens. Conclusion. The results of the experimental studies indicate that ocular hypertension is cocataractogenic factor contributing to the accelerated development of cataract when animals are irradiated with light of high intensity.